The Influence of Work Environment and Transformational Leadership on Job Satisfaction and its Impacts on Employee Performance - Najmudin, Mohamad; Santoso, Indra Budi; Laras, Titi; Helmi, Sulaiman (Migration Letters, 2024)
Employee performance is influenced by various factors. This study aims to analyze the impact of the work environment and transformational leadership on job satisfaction and its subsequent effects on the performance of employees at RSUD Prembun, Kebumen Regency, Central Java. A survey method was employed, with 200 employees serving as respondents selected through stratified random sampling. Data analysis utilized the Structural Equation Model (SEM) to test the research hypotheses. The findings indicate that the work environment and transformational leadership do not directly affect employee performance. However, both the work environment and transformational leadership have a positive influence on employee performance through the mediating factor of job satisfaction. These results align with previous research, emphasizing job satisfaction as a mediating variable, where in this study, satisfaction more effectively mediates the work environment than transformational leadership. The work environment affects job satisfaction but not performance, similarly, transformational leadership influences job satisfaction but not performance. The implementation of a favorable work environment and effective leadership significantly determines job satisfaction.